Ultra-high dose rate FLASH irradiator at the radiological research accelerator facility - Guy Garty; Razib Obaid; Naresh Deoli; Ekaterina Royba; Yuewen Tan; Andrew D. Harken; David J. Brenner (Scientific Reports, 2022)
Abstract The Radiological Research Accelerator Facility has modified a decommissioned Varian Clinac to deliver ultra-high dose rates: operating in 9 MeV electron mode (FLASH mode), samples can be irradiated at a Source-Surface Distance (SSD) of 20 cm at average dose rates of up to 600 Gy/s (3.3 Gy per 0.13 µs pulse, 180 pulses per second). In this mode multiple pulses are required for most irradiations. By modulating pulse repetition rate and irradiating at SSD = 171 cm, dose rates below 1 Gy/min can be achieved, allowing comparison of FLASH and conventional irradiations with the same beam. Operating in 6 MV photon mode, with the conversion target removed (SuperFLASH mode), samples are irradiated at higher dose rates (0.2–150 Gy per 5 µs pulse, 360 pulses per second) and most irradiations can be performed with a single very high dose rate pulse. In both modes we have seen the expected inverse relation between dose rate and irradiated area, with the highest dose rates obtained for beams with a FWHM of about 2 cm and ± 10% uniformity over 1 cm diameter. As an example of operation of the ultra-high dose rate FLASH irradiator, we present dose rate dependence of dicentric chromosome yields.